KELAYAKAN EKONOMI PADA PRARANCANGAN PABRIK FTALAT ANHIDRIDA KAPASITAS 45.000 TON/TAHUN - Diah Anggraeni Jatraningrum; Sari Octavianingrum; Herry Santosa; Didi Dwi Anggoro (Pusbindiklat - LIPI, 2010)
A pre-design of plant to produce 45.000 tons/year phthalic anhydride from 47,200 tons/year ortho-xylene uses Davy McKee process with vanadium pentaoxide catalyst in non isothermal - non adiabatic fixed bed multitubes reactor that operated at 2 atm and 340-360oC. Phthalic anhydride is intermediate chemical that raw material and product price depend on the global economical condition. From the design basis, the economical parameters analysis show that after tax, Profit on Sales (POS) is 7.78%, Return On Investment (ROI) is 34.76%, Pay Out Time (POT) is 2.23 years, Break Event Point (BEP) is 43.71%, Shut Down Point (SDP) is 28.16% and Discounted CashFlow Rate of Return (DCFRR) is 22.40%. All economical parameters requirements for plant design are complied. The range of optimum commercial plant capacity is 26,221 to 71,210 tons/year. Due to price fluctuation, plant can be run normally on range of increasing raw material price +6.79% and decreasing product price -6.92% from price basis and it is better than South East Asia market condition. It is concluded that the phthalic anhydride plant is feasible to be established in Indonesia.